Beispiel Nr: 05
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +3 y =9\\ 3 x -2 y = -6 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 1 x +3 y =9\\ II \qquad 3 x -2 y = -6 \\ I \qquad 1 x +3 y =9 \qquad / \cdot3\\ II \qquad 3 x -2 y = -6 \qquad / \cdot\left(-1\right)\\ I \qquad 3 x +9 y =27\\ II \qquad -3 x +2 y = 6 \\ \text{I + II}\\ I \qquad 3 x -3 x+9 y +2 y =27 +6\\ 11 y = 33 \qquad /:11 \\ y = \frac{33}{11} \\ y=3 \\ \text{y in I}\\ I \qquad 1 x +3\cdot 3 =9 \\ 1 x +9 =9 \qquad / -9 \\ 1 x =9 -9 \\ 1 x =0 \qquad / :1 \\ x = \frac{0}{1} \\ x=0 \\ L=\{0/3\} \end{array} & \begin{array}{l} \\I \qquad 1 x +3 y =9\\ II \qquad 3 x -2 y = -6 \\ I \qquad 1 x +3 y =9 \qquad / \cdot\left(-2\right)\\ II \qquad 3 x -2 y = -6 \qquad / \cdot\left(-3\right)\\ I \qquad -2 x -6 y =-18\\ II \qquad -9 x +6 y = 18 \\ \text{I + II}\\ I \qquad -2 x -9 x-6 y +6 y =-18 +18\\ -11 x = 0 \qquad /:\left(-11\right) \\ x = \frac{0}{-11} \\ x=0 \\ \text{x in I}\\ I \qquad 1 \cdot 0 +3y =9 \\ 3 y +0 =9 \qquad / -0 \\ 3 y =9 -0 \\ 3 y =9 \qquad / :3 \\ y = \frac{9}{3} \\ y=3 \\ L=\{0/3\} \end{array} \end{array} $